EXAMINING THE FACTORS AFFECTING FARMERS WILLINGNESS TO ADOPT AI-DRIVEN SMART FARMING TECHNOLOGIES FOR SUSTAINABLE BANANA CULTIVATION (The Journal of Research ANGRAU, 2025)
The present study explores the willingness of banana farmers in Theni district, Tamil Nadu, to adopt AI technology conducted in 2023. The analysis focuses on the socio-economic and demographic factors influencing the adoption of AI-ML technologies in banana cultivation, with a sample size of 260, analyzed using a multinomial logit model. However, many farmers are efficiently using AI-based mobile applications, soil spectra, drones for fertigation, etc. In Theni, the study tends to identify the reasons for the non-adoption of technologies among the other groups of farmers.The results of the variables like education (0.730), current use of precision farming tools (9.279), understanding of AI (13.18), use of updated irrigation methods (3.950), market price of banana (0.10), and skill (18.877), show a positive and significant effect on the likelihood of willingness to adopt AI technology in banana cultivation. At the same time, the age of the farmer (-0.146), male gender (-3.072), and area (-0.515) have a significant negative impact on the likelihood of AI adoption among farmers. Moreover, experiencedfarmers (-0.253) are still interested in following traditional farming rather than switching to innovative technologies. Innovation is long-termand gradually leads to enhanced profitability and quality production. Therefore, the integration of AI in banana cultivation emerges not only as a transformative technological advancement but as a key catalyst poised to revolutionize productivity, optimize resource allocation, elevate sustainable practices, etc